Requirements for the mass and heating of blanks selection in automated ring-rolling complexes - V. E. Antonyuk; S. G. Sandomirski; V. V. Yavorsky; N. P. Timoshenko; A. V. Budzinskaya (Литьë и металлургия)
The conditions for choosing a billet mass for the manufacture of an ring part on an automated ring-rolling complex, the features of heating the billets in the conditions of an automated line and heat treatment of manufactured parts are considered. The expediency of differentiated assignment of tolerances for the rings’ sizes after ring rolling, depending on their type, conditions of subsequent mechanical treatment and operation, is substantiated. Attention is focused on the need to design a ring-rolling technology with control of the billet parameters not only during the cutting, heating and pressing operations, but also before the ring-rolling operation, especially when using reheating. To evaluate the technological temperature state of the ring blanks at different stages of manufacturing in an automated line, it is offered to use the billet’s “conventional temperature”, which is determined in the 2nd zone from the middle of the billet. The use of single gas heating of billets in rotary-hearth furnaces in the manufacture of annular billet on an automated line is justified. The problems of the automated ring rolling line and the heat treatment complex synchronization are determined. It is shown that the clock capacity of the automated ring rolling line significantly exceeds the clock capacity of the planned heat treatment complex. It is concluded that it is necessary to develop software for their synchronous operation.The proposed recommendations are intended for the development of technological support for an automated ring-rolling complex at OJSC “PAK Plant” as part of “BELAZ-HOLDING”.